“School Unveiling”: The First World Cup in Middle East and Pedagogical Readings from diversity (Praxis Educativa, 2023)
At the end of the 50s, Franz Fanon asks about the binding relationship between certain phenomena of power, identity, gender and resistance, and their forms of simplification/manipulation for the transmission of coloniality. Taking his “Unveiling” political category as a theoretical loan, this paper will try to offer some readings regarding Schools, and the ways they operate, understand and manage diverse and diversity as well. And in order to do so, we will place the First World Soccer Cup that took it place in the Middle East recently, as excuse or a starting point for this historical discussion. It is from this special horizon understood it as part of a political representation, that let us overhaul some frequently relations of inequality that still continues to operate “unseen” between West and East; and that, for us, Schools can urgently attend to help and contribute to counteract them.
Keywords: Schools; Prejudices and Diversity, world soccer cup in Middle East, pedagogical readings, East and West.